The challenges and practice of metal industries into global supply chain integration: A literature review. Issue 1 (1st January 2020) - Dametew, Alie Wube; Beshah, Birehanu; Ebinger, Frank
Abstract: The objective of this study was to investigate the current research practices and existing progress research published on supply chain management and supply chain integration in an attempt to provide a research agenda for future investigations. Mainly the secondary data analysis and methods employed for the investigations. Particularly a systematic literature review analysis from 115 papers published from 16 important journals in the supply chain, logistics, Industrial management & data systems, supply chain management: an international journal and operations management during the period 1997 to 2018 was employed. This paper has identified relevant supply chain integration research studies that have contributed to the development and growth of manufacturing industries performance and competitiveness to the SCI and SCM fields. The analysis of the relevant articles gaps and miss-concepts in the previous literature provides to reduce universality and insufficient ordinary view, confusion of supply chain integrations were investigated. The gaps and investigations were done based on their methodological porches, objectives, analysis and research finding. Mainly the gaps, miss concepts and challenges concepts in the previous literature were identified and grouped in five issues. Moreover, the gaps and recommendations for future research are consolidated into a research agenda that provides practitioners to evaluate existing SCI & SCM issues and seek ways to develop a conceptual farm work on SCI of manufacturing industries to global supply chains.